2018
DOI: 10.3390/nu10030355
|View full text |Cite
|
Sign up to set email alerts
|

Limiting trans Fats in Foods: Use of Partially Hydrogenated Vegetable Oils in Prepacked Foods in Slovenia

Abstract: Consumption of industrially produced trans-fatty acids (TFAs) is a well-established health risk factor that correlates with the increased risk of developing cardiovascular disease. The recommended TFA intake is as low as possible, within the context of a nutritionally adequate diet. Different countries have introduced different measures to minimize the exposure of their population to TFAs. Previous data have shown that TFA content has significantly decreased in Western European countries, while this was not th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 31 publications
2
23
0
Order By: Relevance
“…HO were also less often used in 2017 compared with 2013 (5-2•4 %). These results are consistent with other studies that have observed a decrease in the use of fats and oils containing TFA in recent years (71)(72)(73) . Although for most food categories, a decrease in the use of PHO and HO also showed a decrease in the mean TFA content, we found that in the bakery category, products with PHO, the amount of TFA significantly increased from 0•88 to 2•99 g/100 g in 2017.…”
Section: Discussionsupporting
confidence: 93%
“…HO were also less often used in 2017 compared with 2013 (5-2•4 %). These results are consistent with other studies that have observed a decrease in the use of fats and oils containing TFA in recent years (71)(72)(73) . Although for most food categories, a decrease in the use of PHO and HO also showed a decrease in the mean TFA content, we found that in the bakery category, products with PHO, the amount of TFA significantly increased from 0•88 to 2•99 g/100 g in 2017.…”
Section: Discussionsupporting
confidence: 93%
“…The majority of studies reported on either the choice and acceptability of reformulated foods ( n = 27) 15–30 or nutrient intakes ( n = 26) in the context of reformulation 5,18,24,25,29,31–42 . Only six studies reported on outcomes linked to reduction of NCD burden such as diet‐related risk factors or diseases 43–48 .…”
Section: Resultsmentioning
confidence: 99%
“…In two of these, high TFA levels were confirmed in a previous study [ 34 ]—one in the category biscuits (found in 14 vending machines), and one in the category of crisps and snacks (found in 12 vending machines). It should be noted that since 2019 the amount of TFAs in foods is limited by regulation according to which the maximum permitted TFA level in foodstuffs is 2 g per 100 g of total fat content in the foodstuff [ 20 , 40 ].…”
Section: Resultsmentioning
confidence: 99%